Metal‐Free Directed C−H Borylation of Pyrroles. Issue 15 (5th March 2021) - Wang, Zheng‐Jun; Chen, Xiangyang; Wu, Lei; Wong, Jonathan J.; Liang, Yong; Zhao, Yue; Houk, Kendall N.; Shi, Zhuangzhi
Abstract: Robust strategies to enable the rapid construction of complex organoboronates in selective, practical, low‐cost, and environmentally friendly modes remain conspicuously underdeveloped. Here, we develop a general strategy for the site‐selective C−H borylation of pyrroles by using only BBr3 directed by pivaloyl groups, avoiding the use of any metal. The site‐selectivity is generally dominated by chelation and electronic effects, thus forming diverse C2‐borylated pyrroles against the steric effect. The formed products can readily engage in downstream transformations, enabling a step‐economic process to access drugs such as Lipitor. DFT calculations (wB97X‐D) demonstrate the preferred positional selectivity of this reaction. Abstract : An efficient metal‐free system has been uncovered for the site‐selective C−H borylation of pyrroles by using only BBr3 directed by pivaloyl groups. The site‐selectivity is generally dominated by chelation and electronic effects, thus forming diverse C2‐borylated pyrroles against the steric effect.